Use of a highly specific kinase inhibitor for rapid, simple and precise synchronization of Plasmodium falciparum and Plasmodium knowlesi asexual blood-stage parasites. - Margarida Ressurreição; James A Thomas; Stephanie D Nofal; Christian Flueck; Robert W Moon; David A Baker; Christiaan van Ooij (PLoS ONE)
During the course of the asexual erythrocytic stage of development, Plasmodium spp. parasites undergo a series of morphological changes and induce alterations in the host cell. At the end of this stage, the parasites egress from the infected cell, after which the progeny invade a new host cell. These processes are rapid and occur in a time-dependent manner. Of particular importance, egress and invasion of erythrocytes by the parasite are difficult to capture in an unsynchronized culture, or even a culture that has been synchronized within a window of one to several hours. Therefore, precise synchronization of parasite cultures is of paramount importance for the investigation of these processes. Here we describe a method for synchronizing Plasmodium falciparum and Plasmodium knowlesi asexual blood stage parasites with ML10, a highly specific inhibitor of the cGMP-dependent protein kinase (PKG) that arrests parasite growth approximately 15 minutes prior to egress. This inhibitor allows parasite cultures to be synchronized so that all parasites are within a window of development of several minutes, with a simple wash step. Furthermore, we show that parasites remain viable for several hours after becoming arrested by the compound and that ML10 has advantages, owing to its high specificity and low EC50, over the previously used PKG inhibitor Compound 2. Here, we demonstrate that ML10 is an invaluable tool for the study of Plasmodium spp. asexual blood stage biology and for the routine synchronization of P. falciparum and P. knowlesi cultures.